Ethnicity and prognosis following a cardiovascular event in people with and without type 2 diabetes: Observational analysis in over 5 million subjects in England - Remsing, Sandra C.; Abner, Sophia C.; Reeves, Katharine; Coles, Briana; Lawson, Claire; Gillies, Clare; Razieh, Cameron; Yates, Tom; Davies, Melanie J.; Lilford, Richard; Khunti, Kamlesh; Zaccardi, Francesco (Diabetes research and clinical practice, 2022)
To quantify ethnic differences in the risk of all–cause mortality and cardiovascular disease (CVD) events following a first CVD event in people with and without type 2 diabetes. We identified 5,349,271 subjects with a first CVD between 1 January 2002 and 31 May 2020 in England; CVD included aortic aneurism, cerebrovascular accident, heart failure, myocardial infarction, peripheral vascular disease, and other cardiovascular diseases. We estimated adjusted hazard ratios (HRs) for type 2 diabetes and ethnicity of three outcomes: fatal and nonfatal second CVD event (different phenotype compared to the first) and all–cause mortality. Relative to White, HRs indicated lower rates in all ethnicities and for all outcomes in both men (from 0.64 to 0.79 for all–cause death; 0.78–0.79 for CVD–related death; and 0.85–0.98 for a second CVD event) and women (0.69–0.77; 0.77–0.83; 0.83–0.95, respectively). Irrespective of ethnicity and sex, type 2 diabetes increased rates of all outcomes by around a third. Prognosis following a CVD event was consistently worse in subjects with type 2 diabetes while varied across ethnicities, suggesting the implementation of different strategies for the secondary prevention of CVD in different ethnic groups.